Cerebral atrophy in amyotrophic lateral sclerosis parallels the pathological distribution of TDP43. Issue 2 (15th May 2020) - Dadar, Mahsa; Manera, Ana Laura; Zinman, Lorne; Korngut, Lawrence; Genge, Angela; Graham, Simon J; Frayne, Richard; Collins, D Louis; Kalra, Sanjay
Abstract: Amyotrophic lateral sclerosis is a neurodegenerative disease characterized by a preferential involvement of both upper and lower motor neurons. Evidence from neuroimaging and post-mortem studies confirms additional involvement of brain regions extending beyond the motor cortex. The aim of this study was to assess the extent of cerebral disease in amyotrophic lateral sclerosis cross-sectionally and longitudinally and to compare the findings with a recently proposed disease-staging model of amyotrophic lateral sclerosis pathology. Deformation-based morphometry was used to identify the patterns of brain atrophy associated with amyotrophic lateral sclerosis and to assess their relationship with clinical symptoms. Longitudinal T1 -weighted MRI data and clinical measures were acquired at baseline, 4 months and 8 months, from 66 patients and 43 age-matched controls who participated in the Canadian Amyotrophic Lateral Sclerosis Neuroimaging Consortium study. Whole brain voxel-wise mixed-effects modelling analysis showed extensive atrophy patterns differentiating patients from the normal controls. Cerebral atrophy was present in the motor cortex and corticospinal tract, involving both grey matter and white matter, and to a lesser extent in non-motor regions. More specifically, the results showed significant bilateral atrophy in the motor cortex and corticospinal tract (including the internal capsule and brainstem) and ventricular enlargement, along with significant longitudinal atrophy in precentral gyrus, frontal and parietal white matter, accompanied by ventricular and sulcal enlargement. Atrophy in the precentral gyrus was significantly associated with greater disability as quantified with the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised ( P  < 0.0001). The pattern of atrophy observed using deformation-based morphometry was consistent with the Brettschneider's four-stage pathological model of the disease. Deformation-based morphometry provides a sensitive indicator of atrophy in Amyotrophic lateral sclerosis and has potential as a biomarker of disease burden, in both grey matter and white matter. Abstract : Dadar et al. assess cerebral atrophy in amyotrophic lateral sclerosis and compare the findings with Brettschneider's disease-staging model of amyotrophic lateral sclerosis pathology. The results show significant bilateral atrophy in the motor cortex, corticospinal tract including the internal capsule and brainstem, consistent with the Brettschneider's pathological model. Graphical Abstract: